2013
DOI: 10.4315/0362-028x.jfp-13-155
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Listeria monocytogenes by Propionic Acid–Based Ingredients in Cured Deli-Style Turkey

Abstract: Listeria monocytogenes growth can be controlled on ready-to-eat meats through the incorporation of antimicrobial ingredients into the formulation or by postlethality kill steps. However, alternate approaches are needed to provide options that reduce sodium content but maintain protection against pathogen growth in meats after slicing. The objective of this study was to determine the inhibition of L. monocytogenes by propionic acid-based ingredients in high-moisture, cured turkey stored at 4 or 7°C. Six formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Our results suggest that in high CO 2 environments, organic acids might act synergistically to reduce the growth of L. monocytogenes . The efficacy of organic acids and MAP in L. monocytogenes control in meat and poultry has been also pointed out by other authors [ 7 , 39 , 40 , 41 ]. The effect of lactic acid and MAP on L. monocytog enes in chicken was investigated by Zeitoun and Debevere [ 7 ].…”
Section: Discussionmentioning
confidence: 56%
“…Our results suggest that in high CO 2 environments, organic acids might act synergistically to reduce the growth of L. monocytogenes . The efficacy of organic acids and MAP in L. monocytogenes control in meat and poultry has been also pointed out by other authors [ 7 , 39 , 40 , 41 ]. The effect of lactic acid and MAP on L. monocytog enes in chicken was investigated by Zeitoun and Debevere [ 7 ].…”
Section: Discussionmentioning
confidence: 56%
“…Propionate is a Generally Recognized As Safe (GRAS) antimicrobial and flavoring agent [ 3 ] and its antimicrobial function against L. monocytogenes is under active investigation. Among the variety of food products that have been tested, such as ready-to-eat meat [ 4 , 5 , 6 ], raw poultry [ 7 ], and produce [ 8 , 9 ], propionate exhibited anywhere from no effect [ 7 , 8 ] to a significant growth inhibitory effect [ 4 , 5 ]. While the exact conditions required for propionate to inhibit L. monocytogenes growth are not clear in food products, it was shown that the presence of propionate at concentrations as little as 4 mM could decrease L. monocytogenes in vitro growth in rich media [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glass et al (10) also reported that inclusion of 0.2 or 0.3% sodium propionate supported a < 1.0-log increase of L. monocyto genes in ham and uncured turkey breast over 120 days of storage at 4°C. More recently, Glass et al (11) reported that inclusion of sodium propionate at 0.3, 0.4, or 0.5% in cured turkey breast precluded growth of L. monocytogenes (< 1.0log increase) during 63 days of storage at 4°C when compared with otherwise similar samples formulated without antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the efficacy of growth inhibitors for reducing the risk and occurrence of L. monocytogenes could be affected by meat type (i.e., poultry versus pork), intrinsic characteristics of the product (e.g., pH, water activity, moisture, or nitrite level), and concen tration of the antimicrobial and/or its dissociation constant (i.e., pKa) (5,11,30). For example, typical concentrations of lactate (1.5 to 3.0%) used alone or in combination with diacetate (0.125 to 0.25%) by meat processors are less effective for suppressing outgrowth of L. monocytogenes on uncured RTE meats than on cured RTE products (10,37), most likely because of the synergistic effect of nitrite and lactate-diacetate in the cured products.…”
mentioning
confidence: 99%